Looking Behind the Screen: Genealogies of Poetic Technology. (26th December 2019) - Middleton, Peter
Abstract: Everyone, from distinguished philosophers to emergent poets, has been to some extent disoriented by the new digital technology and its shimmer of compositional novelty. This article reviews recent studies of the impact of the digital on research into the history of modern and contemporary poetry. Almost all poetry written and circulated today is dependent on digital media, with profound consequences for every aspect of its writing, performance, and reception. I argue that scholars of poetry can benefit from learning more about what constitutes the digital, as material technology, as programming, and as transformative social practice, as well as by studying earlier phases of the rapid transformation of communications technology. I then discuss briefly several recent texts on current digital infrastructure, before surveying some representative recent critical works that draw on insights derived from our digital era to provide new perspectives on the predigital age of poetry. At the heart of this review, essay is extended discussions of Seth Perlow's The Poem Electric and Todd Tietchen's Technomodern Poetics, recent books that explore changing concepts of lyric, surveillance, anonymity, and even electricity. In addition, this essay discusses The Bloomsbury Handbook of Electronic Literature, edited by Joseph Tabbi, which has a strong focus on poetics.